Maternal home care for premature and/or low birth weight children born during the pandemic (Research, Society and Development, 2022)
The study aimed to elucidate the maternal care of preterm and/or low birth weight children at home during the coronavirus pandemic. This is a qualitative study, supported by Symbolic Interactionism, developed in a philanthropic maternity hospital in a city in the interior of São Paulo. Data collection took place from March of September 2021. Ten women, mothers of premature and/or low birth weight children, were interviewed. The Thematic Analysis guided the appreciation of the data. Among the findings, reflections and behaviors were present, in the centrality of care, in order to protect the child from contamination by SARS-CoV-2. The themes “Living with uncertainties during pregnancy, childbirth and birth”, “Social interactions promoting reflections on the chances of contamination”, “Efforts to control the chances of contamination” and “Protection immersed in fears” emerged during the data analysis. It was concluded that the establishment of child care was governed by the fear of contamination by the coronavirus. Thus, it was evident that it is up to the nurse, both in hospital care and in primary care, to support the mother of a child born at risk and to structure their care considering the particularities of the insertion context. Specifically, in the Covid-19 pandemic, the child's susceptibility to infections and a scenario prone to the transmission of the coronavirus, are put in relation.